Investigation of In-Gap Field Enhancement at Terahertz Frequencies for a Metasurface Enhanced Sensor - Tugay, Halime; Altan, Hakan; Demirhan, Yasemin; Demirhan, Yasemin; Özyüzer, Lütfi; Özyüzer, Lütfi; Sabah, Cumali (Institute of Electrical and Electronics Engineers, 2021)
The arrangements of subwavelength inclusions in a metasurface can serve as an effective absorber for the terahertz region. When such an absorber is combined with a unique material, the absorption can induce effects that can lead to a change in the materials electrical properties. Vanadium dioxide shows a passive and reversible change from monoclinic insulator phase to metallic tetragonal rutile structure by using external stimuli such as temperature (340K), photo excitation, electric field, mechanical strain or magnetic field [1,2]. Upon absorption of the THz radiation, the high electric fields that are generated inside the gaps of the metasurface can serve as trigger points, as was shown previously using kV strength THz E-fields.
Keywords: Temperature sensors; Vanadium compounds; Terahertz radiation